Outlook for Neurofi bromatosis Type I Research in the Republic of Bashkortostan - R. N. Mustafin; E. K. Khusnutdinova (Креативная хирургия и онкология)
Neurofi bromatosis type I (NF1) is a common hereditary tumour syndrome with autosomal dominant type of inheritance. Average worldwide incidence rate of NF1 is 1:3000, equal in men and women. Th e disease develops with a heterozygous mutation in the oncosupressor neurofi bromin-encoding gene NF1. No NF1-associated most common mutations have been found, with over 1400 mutations being described along the gene. No clinical and genetic correlations are observed for NF1, and its symptoms may vary considerably within same inheritance group. Typical NF1 manifestations include pigmented patches and multiple cutaneous or subcutaneous neurofi bromas, oft en disfi guring in degree. Pathogenetic therapy for NF1 is not yet developed, whilst surgical tumourectomy may lead to recurrence and new tumour development in other localities on the body. Molecular genetic research on putative interfaces with epigenetic factors and gene expression patterns may open promising future avenues. Further, establishing a marker NF1 mutation in NF1 patients will allow secondary prevention of the disease. A survey of russian NF1-related literature reveals prevalence of individual clinical case descriptions. In the Russian Federation, studies of NF1-associated mutations in gene NF1 originate from Moscow and Bashkortostan, which sets off advancement of Bashkir medical genetics and urges further developments. In Bashkortostan, 10 NF1-associated mutations were described from 16 patients. Th e reported mutations с.1278G>A (p.Trp426Х), с.1570G>A (p.Glu540Lys), с.1973_1974delTC (р.Leu658ProfsX10), с.3526_3528delAGA (p.Arg1176del), с.3826delC (р.Arg1276GlufsX8), с.4514+5G>A, c.5758_5761delTTGA (p.Leu1920AsnfsX7) in the NF1 gene are new to science. Further research into other genes’ and microRNA expression in patients with various clinical manifestations of NF1 should be aimed at discovering its possible involvement in disease pathogenesis.